Case report: Impact of hyperthyroidism on psychotic symptoms in schizophrenia comorbid with Graves’ disease - Sumi, Yukiyoshi; Kawahara, Sanae; Fujii, Kumiko; Yamaji, Mayu; Nakajima, Kou; Nakamura, Tsubasa; Horikawa, Osamu; Fujita, Yukihiro; Ozeki, Yuji (Frontiers in Psychiatry, 2023)
Introduction: Auditory hallucinations are the most common type of hallucinations observed in schizophrenia; however, visual hallucinations are not uncommon. In Graves' disease, depression, hypomania, and psychosis can occur. While the association between Graves' disease and psychosis has been explored, understanding of the specific impact of thyroid dysfunction severity on psychiatric symptom severity is limited. Here, we present a case report of a patient with schizophrenia comorbid with Graves' disease whose psychotic symptoms were impacted by hyperthyroidism.The patient was a 32-year-old Japanese woman who presented with auditory and visual hallucinations, agitation, and pressured speech. The patient was diagnosed with schizophrenia comorbid with Graves' disease and thyroid storm. The patient's psychotic symptoms were found to be associated with fluctuations in thyroid hormone levels, and visual hallucinations were observed only during thyroid storms. Treatment involved dexamethasone, potassium iodide, bisoprolol fumarate, and methimazole for thyrotoxicosis, and a blonanserin transdermal patch, paliperidone, and paliperidone palmitate for psychotic symptoms. The patient's auditory and visual hallucinations improved with antipsychotic treatment and decreased thyroid hormone levels. Conclusion: This case highlights the importance of monitoring thyroid function in patients with schizophrenia, particularly those with comorbid Graves' disease. The correlation between psychiatric symptoms and thyroid hormone levels was demonstrated on an individual level over time, with symptoms worsening as thyroid hormone levels increased. Additionally, our case suggests that abnormally high thyroid hormone levels may trigger visual hallucinations in individuals with schizophrenia. Further studies are needed to elucidate the underlying mechanisms and potential treatment implications of this association.